Nasal In situ Gel Systems For Enhanced Drug Delivery: A Comprehensive Review - Pahurkar A. Ashwin; Dr. Nishan N. Bobade; Dr. Shrikant D. Pande; Wakte , Dr.Pravin; Dr. Sandeep C Atram; Dr. Vikrant P. Wankhade (Asian Journal of Pharmaceutical Research and Development, 2026)
Intranasal delivery has emerged as a promising alternative route for drug administration due to its non-invasive nature, rapid absorption, and ability to bypass hepatic first-pass metabolism. In recent years, nasal in-situ gel systems have gained considerable interest as they offer improved retention time and controlled drug release within the nasal cavity. These systems are designed to be administered as low-viscosity liquids that convert into gels upon contact with physiological conditions such as temperature, pH changes, or ions present in nasal secretions. This sol-to-gel transition enhances mucoadhesion, minimizes the chances of formulation drainage, and ensures prolonged interaction of the drug with the nasal mucosa, thereby increasing therapeutic efficiency. Different polymers such as Poloxamers, Carbopol, Gellan gum, and Sodium alginate are widely used in these formulations due to their stimuli-responsive gelling properties and biocompatibility. The ideal nasal in-situ gel should possess optimal viscosity for easy administration, suitable gel strength for retention, and must maintain clarity, stability, sterility, and uniform drug content. Such formulations have demonstrated significant potential in delivering a broad range of therapeutic agents including analgesics, anti-inflammatory drugs, peptides, vaccines, and central nervous system (CNS) active compounds, especially where rapid and sustained action is desired. Evaluation of nasal in-situ gels involves assessing parameters like gelling capacity, viscosity, gel strength, drug release behavior, isotonicity, sterility, and stability studies to ensure safety and effectiveness. Overall, nasal in-situ gel technology offers a versatile and patient-friendly platform capable of improving drug bioavailability and enhancing clinical outcomes for various therapeutic applications.